Answer: Option c.
Step-by-step explanation:
You need to use the following Kinematic equation:
![V_f=V_0+at](https://img.qammunity.org/2020/formulas/physics/middle-school/2u8ofknylj3d3pwlamq6x3fc2w9i52ru5c.png)
Where
is the final velocity,
is the initial velocity,
is the acceleration and
is the time.
In this case, you can identify that:
![V_0=0\ (it\ accelerates\ from\ rest)\\\\a=50.0\ (m)/(s^2)\\\\t=1\ min=60\ s](https://img.qammunity.org/2020/formulas/physics/college/mm5zrgdbs8ufj8qukupdnim3ee2f5ttvg2.png)
Therefore, substituting these values into the formula, you get:
![V_f=0+(50.0\ (m)/(s^2))(60\ s)\\\\V_f=3,000\ (m)/(s)\\\\V_f=3.00*10^3\ (m)/(s)](https://img.qammunity.org/2020/formulas/physics/college/m4brb9olkhjch7iu627qe25fzoix2x1p3d.png)